Economics : student workbook and reader - Sloman, John, 1947-; Sutcliffe, Mark, M.Sc. (Harlow, England ; New York : Prentice Hall/Financial Times, 2003)
Suitable as an accompaniment to any introductory economics text, but designed to be used specifically with John Sloman's text, this student workbook encourages the reader to delve into the subject and analyse typical economics problems and situations.
Includes bibliographical references and index.
oif 04/11/14
Loan
Keywords: Economics